Spiritual Friendship and Bridal Mysticism in an Age of Affectivity - Stefaniw, Blossom (Cistercian studies quarterly, 2006)
The article discusses the distinction between Cistercian love spiritually and the age of courtly love in terms of sources and respective conceptual structures. A triangular comparison was made of Ælred's love ideal as represented in his "Spiritual Friendship," Saint Bernard's bridal mysticism in his "Sermons on the Song of Songs" and the courtly love ideal. Although love plays a central role in Cisterian spirituality, it is not clear to what degree their concentration on love was determined or defined by contemporary ideals.